The evolution of financial models in the community - Haidukova, Julia; Trygub, Inna (My University, 2014)
A particular model asanexampleofthe evolution of financial models in the communityis a Chinese model of economic growth. Chinese model has important features. The first, most unique, large population and vast territor. Second - the largest state under the rule of the Communist Party, a key in the Chinese model, that it has identified an opportunity for reform. The third - a large part of the ethnic Chinese of foreign capital and the existence of entire nations of the Chinese population. These basic features of the Chinese model in conjunction with the Chinese reforms make China a success. So we can conclude that the Chinese financial model in part suitable for Ukraine.
Keywords: financial relations; financial model; experience; government policy; China; фінансові стосунки; фінансова модель; досвід; урядова політика; финансовые отношения; финансовая модель; опыт; правительственная политика; Китай; кафедра ділової іноземної мови та міжнародної комунікації